The Return of the Surreal: Towards a Poetic and Playful Sociology - Foster, Victoria (Qualitative Sociology Review, 2019)
This article argues that the time is ripe to reacquaint sociology and surrealism. Taking inspiration from surrealism’s emphasis on making the ordinary strange through bizarre, lively and sometimes haunting methods might result in a more poetic and playful sociology. The article looks at how this might be applied in practice through drawing on a variety of examples of social research that share some of the tenets of surrealism, not least the latter’s focus on social justice. This enables discussion of a number of methodological concerns stemming from feminist and post-structuralist thought, including the troubling of narrative coherency and the notion of “voice.” Infusing sociology with “a surrealist spirit” requires opening up and moving away from rationality in ways that allow for the exploration of contradictions, irreverence, humor, and paradox.